2020
DOI: 10.1016/j.sapharm.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist led medication reviews in the UK: A scoping review of the medicines use review and the new medicine service literatures

Abstract: Community pharmacist led medication reviews in the UK: a scoping review of the medicines use review and the new medicine service literatures. Research in Social & Administrative Pharmacy, 16 (2). pp. 111-122.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…Few studies have assessed the time invested in this service, which is an important factor considering the cost involved. Lee et al [42] obtained a median time required for pharmacists to perform the initial MUR visit very similar to our results, although a scoping review of the medicines use review reported that the MUR consultations were short, typically 10-12 min [43]. Our results show that there was a significant correlation between the MUR time and number of medicines.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have assessed the time invested in this service, which is an important factor considering the cost involved. Lee et al [42] obtained a median time required for pharmacists to perform the initial MUR visit very similar to our results, although a scoping review of the medicines use review reported that the MUR consultations were short, typically 10-12 min [43]. Our results show that there was a significant correlation between the MUR time and number of medicines.…”
Section: Discussionsupporting
confidence: 88%
“…The purposes of MURs are to improve patients' understanding of their medicines and adherence, particularly among those with chronic conditions, highlight problematic side effects and propose solutions where appropriate, and to reduce medicines wastage. 3 Similarly, in Canada, pharmacist provides "medication management", a comprehensive pharmacy service that helps optimize health outcomes and patients targeted medication outcomes. In Canada, this service is offered to residents taking at least one medication.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 There has been limited empirical investigation of the outcomes or patients' perspectives of these services. 6 A randomised controlled trial of the NMS found self-reported medicines adherence increased by 10% after 10 weeks. 7 Qualitative work within this trial found that the NMS was simplified and adapted in its implementation to fit with pharmacists' existing workloads.…”
Section: Introductionmentioning
confidence: 99%